A Case Study: The Effects of Restorative Justice Course on African-American Students in an Urban School. - (:unkn) unknown (My University, 2018)
This ethnographic critical case study investigated the usefulness of a restorative justice course as an alternative to punitive discipline in a high school setting, the goal of which was to holistically address ways to effectively deal with conflict, safety and wellness issues of African-American students in an urban high school. The researcher has worked closely with the school and identified the strengths of an under-utilized approach that has the potential to completely eradicate excessive suspensions and expulsions. Given the research purpose of studying a model of discipline with possible replication at other sites, the research approach was that of a single critical case study employing methods of document analysis, observation, and individual interviews. Alternative approaches to discipline in urban school settings is sporadic and is rarely promoted with concerns of its gentle nature and inability to be retributive. For the purposes of this study, the term alternative was used as an umbrella term to encompass the multiple facets of restorative justice and the impact it has on school cultures, differences in organizational practices, mutual engagement, dialogue, negotiation, power, and joint problem solving. While there is growing support for restorative practices in school settings around the globe, the evidence for their effectiveness is somewhat mixed. ii Given the importance of equitable learning as a common strategy in teaching students in an urban environment, this research study attempted to understand in detail the effectiveness of a restorative justice model used successfully in an urban school. The research indicates both students and staff responded positively to the use of restorative practices at this urban high school. Suspensions were limited, the student attendance rate was high, and academic success was above average as compared to other schools in the district. Relationships between students and staff were strong, as well as the relationships between students. Restorative practices were not only used at the high school, but were extended in many of the students’ homes and communities. Moreover, restorative practices were successfully used as an alternative to punitive discipline approaches. The study describes and documents the unfolding of these practices. The focus of the research was to investigate the lived experiences of the 2017-2018 12th grade students and staff at one urban high school that implemented a program of restorative practices with fidelity in order to eliminate excessive suspensions and expulsions. The research extends the study findings to discuss the nature of learning in this context as well as the implications for teachers in facilitating peacekeeping circles and repair harm circles in their classroom.
Keywords: Alternative Discipline; Black Students; Discipline; Education; Education Policy; Incarceration